The prion-like characteristic of ORF3 contributes to virion release and pathogenesis of hepatitis E virus - Yajing Wang; Houlu Tian; Na Shi; Chunyan Wu; Yaowei Huang; Yongling Yang; Qiang Ding; Xu Zheng; Qin Zhao; Zhaonong Hu; Jiaojiao Luo; Lele Feng; et al. (Proceedings of the National Academy of Sciences, 2025)
Hepatitis E virus (HEV), the causative agent of hepatitis E, is threatening public health globally. Due to the shortage of efficient in vitro cell culture systems and in vivo model, the viral replication and pathogenesis mechanisms remain largely unknown. Here, we found that HEV-ORF3 protein showed prion-like properties in HEV-infected cells and existed as both monomer and SDS-resistant aggregate forms. In an in vitro cell-free model, incubation of ORF3 monomer with its aggregates could effectively convert ORF3 monomer into aggregates, mirroring a typical characteristic of prion. In addition, the prion domain (PrD) of a classic yeast prion Sup35 could be functionally replaced by full-length HEV-ORF3 or its N-terminal candidate PrD (cPrD). An F10S substitution in the ORF3-cPrD impaired HEV-ORF3 aggregation propensity and blocked the function of ORF3 in enhancing the stability of microtubules in HEV-infected cells, thus led to the inhibition of viral capsid translocation to microtubules and virion release from infected cells. In Mongolian gerbil models, HEV bearing ORF3F10S mutation demonstrated attenuated virulence in vivo compared with wild-type HEV, as evidenced by reduced viremia and viral shedding, as well as alleviated pathological changes of liver tissue in gerbils infected by HEV-ORF3F10S mutant. In conclusion, our data suggest that HEV-ORF3 is a prion-like protein which is involved in viral capsid translocation and virion release, supporting the hypothesis that the self-propagating properties of prion proteins or prion-like proteins are widely exploited in nature and play diverse roles in physiological function.